Sustainable agriculture : advances in technological interventions - Singh, Ajoy Kumar (Agronomist); Patel, Vishwa Bandhu (Burlington, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2020)
"This new volume looks at the evolution and challenges of sustainable agriculture, a field that is growing in use and popularity. Sustainable Agriculture: Advances in Technological Interventions discusses some of the important ideas, practices, and policies that are essential to an effective sustainable agriculture strategy. The book features 25 chapters written by experts in related fields, including crop improvement, natural resource management, crop protection, social sciences, and product development. The volume aims to provide a good understanding of the use of sustainable agriculture and the sustainable management of agri-horticultural crops, focusing on eco-friendly approaches, such as the utilization of waste materials. Topics include ecofriendly plant protection measures, climate change and natural resource management, tools to mitigate the effect of extreme weather events, agrochemical research and regulation, soil carbon sequestration, water and nutrient management in agricultural systems, and more. Key features: discusses sustainable agriculture within the framework of recent challenges in agriculture Looks at the development and diversification of crops and cultural practices to enhance biological and economic stability; features the application of innovative nanotechnologies to agricultural research and production technologies; highlights the development of new varieties in agri-horticultural crops in relation to biotic and abiotic management; discusses the application of recent technologies for soil-plant-microbe-environment interactions."--
Genetic Improvement of Major Cereals in Prospect to Bihar State / P. K. Singh, Anand Kumar, and Ravi Ranjan Kumar -- Status, Opportunities, and Challenges of Spice Research and Development / Sangeeta Shree and Paramveer -- Perspective of Plantation Crops with Special Reference to Coconut and Palmyra / Ruby Rani, V. B. Patel, and H. P. Maheshwarappa -- Overview of the Floriculture Sector: Performance, Problems, and Prospects / Paramveer Singh, Sangeeta Shree, and Ajay Bhardwaj -- Climate Change and Natural Resource Management / Suborna Roy Choudhury and Syed Sheraz Mahdi -- Soil Carbon Sequestration: Particular Reference to Bihar / Rajeev Padbhushan, Anupam Das, and Swaraj Kumar Dutta -- Agromet Advisory Services: Tool to Mitigate the Effect of Extreme Weather Events / Sunil Kumar -- Soil Pollution: Studies with Specific Reference to Bihar / M. K. Dwivedi, S. Kumar, A. Kohli, Y. K. Singh, S. Shambhavi, and R. Kumar -- Nanotechnology in Agricultural Science / Nintu Mandal, Kasturikasen Beura, and Abhijeet Ghatak -- Endomycorrhizal Fungi: Phosphorous Nutrition in Crops / Mahendra Singh, Rajiv Rakshit, and Kasturikasen Beura -- Water Management in Horticultural Crops / K. Karuna and Abhay Mankar -- Orchard Floor Management / Manoj Kundu -- High-Density Planting in Fruit Crops for Enhancing Fruit Productivity / V. K. Tripathi, Sanjeev Kumar, Vishal Dubey, and Md. Abu Nayyer -- Enriching Vermicompost Using P-Solubilizing and N-Fixing Biofertilizers and Eco-Friendly Low-Cost Minerals / Arun Kumar Jha -- Protected Horticulture in India: An Overview / Paramveer Singh, Ajay Bhardwaj, and Randhir Kumar -- Use of Fly Ash in Agriculture / Sankar Ch. Paul -- Natural Resource Management and Land Use Planning / C. D. Choudhary, B. K. Vimal, Shweta Shambhavi, and Rajkishore Kumar -- Plant Disease Management Through Application of Nanoscience / Abhijeet Ghatak -- Status of Insect Pests of Cereals in India and Their Management / Anil Gautam Kunal and Tarak Nath Goswami -- Major Insect Pests of Vegetable Crops in Bihar and Their Management / Tamoghna Saha, Nithya Chandran, and B. C. Anu -- Emerging Viral Diseases of Vegetable Crops: An Outline and Sustainable Management / Mohammad Ansar, A. Srinivasaraghavan, and Anirudd/ha Kumar Agnihotri -- Advancement of Agrochemical Research and Regulation / Pritam Ganguly -- Institutional Outreach Through Innovative Approaches / Aditya and R. K. Sohane -- An Appraisal on Quality Honey Production / Ramanuj Vishwakarma and Ranjeet Kumar -- Empowering Rural Youth Through Agripreneurship / Ram Datt.
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable agriculture; SCIENCE / General; SCIENCE / Life Sciences / Botany; TECHNOLOGY / Agriculture / General